An Introduction to Architectural Theory : 1968 to the Present - Mallgrave, Harry Francis, 1947-; Goodman, David, 1974- (Malden, MA : Wiley-Blackwell, 2011)
'A sharp and lively text that covers issues in depth but not to the point that they become inaccessible to beginning students, An Introduction to Architectural Theory is the first narrative history of this period, charting the veritable revolution in architectural thinking that has taken place, as well as the implications of this intellectual upheaval. The first comprehensive and critical history of architectural theory over the last forty years surveys the intellectual history of architecture since 1968, including criticisms of high modernism, the rise of postmodern and poststructural theory, critical regionalism and tectonics Offers a comprehensive overview of the significant changes that architectural thinking has undergone in the past fifteen years Includes an analysis of where architecture stands and where it will likely move in the coming years'--
'An Introduction to Architectural Theory is the first comprehensive and critical history of architectural theory over the last forty years. Mallgrave employs the words theory and architecture in a broad sense--the latter encompassing aspects of urban planning, structural, and landscape design, while theory too is often indistinguishable from practice. The text surveys the intellectual history of architecture since 1968, including criticisms of high modernism, the rise of postmodern and poststructural theory, critical regionalism and tectonics, and the significant changes that architectural thinking has undergone in the past fifteen years, concluding with an analysis of where architecture stands and where it will likely move in the coming years. A sharp and lively text that covers issues in depth but not to the point that they become inaccessible to beginning students, An Introduction to Architectural Theory is the first narrative history of this period, charting the veritable revolution in architectural thinking that has taken place, as well as the implications of this intellectual upheaval'--
Includes bibliographical references (pages 231-264) and index.
Keywords: Architecture -- Philosophy; Architecture -- Historiography